Inhibition of cyclooxygenase‐2 enhanced intestinal epithelial homeostasis via suppressing β‐catenin signalling pathway in experimental liver fibrosis. Issue 16 (19th June 2021) - Zhang, Linhao; Tai, Yang; Zhao, Chong; Ma, Xiao; Tang, Shihang; Tong, Huan; Tang, Chengwei; Gao, Jinhang
Abstract: The intestinal barrier dysfunction is crucial for the development of liver fibrosis but can be disturbed by intestinal chronic inflammation characterized with cyclooxygenase‐2 (COX‐2) expression. This study focused on the unknown mechanism by which COX‐2 regulates intestinal epithelial homeostasis in liver fibrosis. The animal models of liver fibrosis induced with TAA were established in rats and in intestinal epithelial–specific COX‐2 knockout mice. The impacts of COX‐2 on intestinal epithelial homeostasis via suppressing β‐catenin signalling pathway were verified pharmacologically and genetically in vivo. A similar assumption was tested in Ls174T cells with goblet cell phenotype in vitro. Firstly, disruption of intestinal epithelial homeostasis in cirrhotic rats was ameliorated by celecoxib, a selective COX‐2 inhibitor. Then, β‐catenin signalling pathway in cirrhotic rats was associated with the activation of COX‐2. Furthermore, intestinal epithelial–specific COX‐2 knockout could suppress β‐catenin signalling pathway and restore the disruption of ileal epithelial homeostasis in cirrhotic mice. Moreover, the effect of COX‐2/PGE2 was dependent on the β‐catenin signalling pathway in Ls174T cells. Therefore, inhibition of COX‐2 may enhance intestinal epithelial homeostasis via suppression of the β‐catenin signalling pathway in liver fibrosis.